Organizational Citizenship Behavior sebagai Mediator antara Kecerdasan Spiritual, Kecerdasan Emosional, dan Kinerja Pegawai - Desy Sulipatty; Mohamad Arsad Rahawarin; Zainal Abidin Rengifurwarin (MAN 4 Kota Pekanbaru, 2025)
This study examines the influence of spiritual intelligence and emotional intelligence on employee performance through organizational citizenship behavior (OCB) at the Youth and Sports Office of West Seram Regency. Using a quantitative associative design with a cross-sectional approach, all 21 employees were included through full sampling. Data were analyzed using path analysis with SPSS 25. The results show that both spiritual and emotional intelligence significantly enhance OCB, yet neither has a direct effect on employee performance. OCB, however, directly improves performance and serves as a mediating variable that connects both forms of intelligence to performance. These findings indicate that spiritual and emotional capacities contribute to better performance only when manifested through voluntary, proactive, and citizenship-oriented behaviors within the organization.